Epi-Sarsasapogenin and epi-smilagenin: two sapogenins isolated from the rumen content of sheep intoxicated by Brachiaria decumbens - Lajis, Nordin H.; H. Abdullah, A.Salam; S. Salim, S.Jalaludin; Bremmer, John B.; Khan, Mohammad Niyaz (Elsevier, 1993)
Spectroscopic examinatio of purified extracts of the rumen content of sheep intoxicated by Brachiaria decumbens revealed the presence of two spirostanes, identified as epi-sarsasapogenin and epi-smilagenin. Sarsasapogenone was obtained by the oxidation of sarsasapogenin. The reduction of sarsasapogenone using lithium aluminum hydride yielded isomeric products, sarsasapogenin (20%) and epi-sarsapogenin (80%). © 1993.